1993
DOI: 10.2307/3431868
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Proliferating Cell Nuclear Antigen to Tritiated Thymidine As a Marker of Proliferating Hepatocytes in Rats

Abstract: Proliferating cell nuclear antigen (PCNA), an endogenous nuclear protein, has recently been used to identify replicating cells. PCNA was compared to tritiated thymidine ([3Hl-TdR), a reliable and accurate exogenous labeling agent, to ascertain if PCNA gives comparable results for quantitative cell proliferation. Male F344 rats were treated with a single dose of 500 mg/kg 4-acetylaminofluorene (4-AAF), a known liver mitogen. Rats (n = 5) were euthanized and necropsied at 6, 12, 18, 24, 36, 48, 96, or 192 hr af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 16 publications
(16 reference statements)
2
27
0
3
Order By: Relevance
“…Previous studies have demonstrated that immunohistochemical staining patterns of PCNA, using paraffin-embedded liver tissue sections, are comparable to tritiated thymidine incorporation in rodents, suggesting that the nucleus alone shows positive reactivity in G1 phase and strong positive reactivity in S phase, but neither the nucleus nor the cytoplasm of hepatocytes shows a positive reaction in G0 phase (Foley et al 1993). In the present study, the labeling index of BrdU, analogous to tritiated thymidine, and the proportion of PCNA-stronglypositive hepatocytes were equally reduced in DR in vivo, while the proportion of neither PCNA-positive hepatocytes nor TUNEL-positive hepatocytes was influenced 366 Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have demonstrated that immunohistochemical staining patterns of PCNA, using paraffin-embedded liver tissue sections, are comparable to tritiated thymidine incorporation in rodents, suggesting that the nucleus alone shows positive reactivity in G1 phase and strong positive reactivity in S phase, but neither the nucleus nor the cytoplasm of hepatocytes shows a positive reaction in G0 phase (Foley et al 1993). In the present study, the labeling index of BrdU, analogous to tritiated thymidine, and the proportion of PCNA-stronglypositive hepatocytes were equally reduced in DR in vivo, while the proportion of neither PCNA-positive hepatocytes nor TUNEL-positive hepatocytes was influenced 366 Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Immunohistochemistry for bromodeoxyuridine (BrdU) (Shimokawa et al 1997) and proliferating cell nuclear antigen (PCNA) (Foley et al 1993;Higami et al 1997a) was performed to evaluate the proliferation of hepatocytes. Immunohistochemistry for bromodeoxyuridine (BrdU) (Shimokawa et al 1997) and proliferating cell nuclear antigen (PCNA) (Foley et al 1993;Higami et al 1997a) was performed to evaluate the proliferation of hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…PCNA staining was performed according to a modification of the protocol of Foley et al (5). Briefly, the slides were dried overnight, deparaffinized through three changes of xylene, hydrated to distilled water, and incubated with PC-10 antibody (Novocastra Laboratory, Newcastle-on-Tyne, UK) in capillary gap slides at 35°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…A labeling index was obtained by counting 1000 hepatocytes/rat. Additional sections were stained immunohistochemically for the endogenous replication marker, proliferating cell nuclear antigen (PCNA) [10,11], using a PCNA monoclonal antibody (Coulter Corporation, Hialeah, FL) and an antimouse IgM biotinylated secondary antibody (Vector Laboratories) followed by streptavidin and 3,3-diaminobenzidine. A proliferating index was obtained based on 1000 hepatocytes/rat.…”
Section: Assessment Of Hepatocellular Proliferationmentioning
confidence: 99%